War and forced displacement through illustrated albums: Theoretical review and didactic proposal to work in primary education - Roldán Farrés, Mònica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Every day, war, ideological persecution and violence in the streets force millions of families to leave their homes. Children and youth literature and, specifically, illustrated albums, become a fundamental teaching tool for working on complex issues such as war and forced displacement in the classroom. Taking this into account, are there illustrated albums dedicated to these topics? How can we take advantage of them in the classroom? The present work aims to answer these questions from a concrete practical proposal and a theoretical approach to the concepts that concern it.